Effects of Standardized Ileal Digestible Lysine Level on Growth Performance in 170 to 220 lb DNA Finishing Pigs - Rafe Q. Royall; Robert D. Goodband; Mike D. Tokach; Joel M DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to estimate the SID Lys requirement for growth and feed efficiency of 170- to 220-lb finishing pigs. A total of 616 barrows and gilts (600 × 241, DNA; initially 168.3 ± 2.7 lb BW) were used in two separate studies each lasting 21 d. Pens of pigs were blocked by BW and randomly allotted to 1 of 7 dietary treatments with 8 to 10 pigs per pen in a randomized complete block design. A similar number of barrows and gilts were placed in each pen. Dietary treatments were corn-soybean meal-based and formulated to 0.58, 0.65, 0.72, 0.79, 0.86, 0.92, and 1.00% SID Lys. There were 11 replications per treatment for levels of 0.65, 0.72, 0.79, 0.86, and 0.92% SID Lys; 6 replications for the 0.58% SID Lys treatment; and 5 replications for the 1.00% SID Lys treatment. Increasing SID Lys increased (linear,P= 0.022) ADG. Feed efficiency (quadratic,P= 0.034) improved, while Lys intake/d, and Lys intake/kg of gain increased (linear,P<0.001) with increasing SID Lys. At both high and low ingredient and pig prices, feed cost per pig (linear,P<0.001) and feed cost/lb gain increased (quadratic,P<0.05), and total revenue per pig tended to increase (linear,P= 0.051) as SID Lys increased. However, at both high and low ingredient and pig prices, there were no differences in income over feed cost (IOFC) among dietary treatments. The broken-line linear model to maximize ADG predicted that there was no further improvement to ADG past 0.83% and for F/G, the quadratic polynomial model predicted a requirement of 0.90% SID Lys. However, similar fitting linear models predicted maximum ADG and F/G greater than 1.00% SID Lys. Income over feed cost at high ingredient and pig prices was predicted by the QP model to be maximized at 0.78% SID Lys. Meanwhile, at low ingredient and pig prices, the BLL model predicted maximum IOFC at 0.76% SID Lys, or lower. In summary, the optimal SID Lys level for finishing pigs from 170 to 220 lb depends upon the response criteria, with growth performance maximized between 0.83 to 0.90% SID Lys. Income over feed cost was maximized at 0.78% SID Lys or lower.
Keywords: amino acid; growth; lysine requirement; finishing pig